Manajemen Preoperatif dan Anestesia Pasien Geriatri - Dita Mauliana Prabiwi; Ari Wahyuni (CV. Jasa Sukses Abadi, 2021)
Geriatric patients are elderly patients over 60 years of age and have multi-pathological characteristics whose symptoms are atypical with decreased physiological reserve and are usually accompanied by functional disorders. Up to 60 years of age, both basal organ function and physiological reserve are well preserved. Furthermore, the physiological reserve function will decrease. In addition to the pharmacokinetic changes in drug metabolism associated with aging, pharmacodynamic changes can also alter drug response in geriatric patients. The preoperative evaluation and assessment in elderly patients is usually more complex than in younger patients because of the heterogeneity and the increased frequency and severity of comorbidities associated with aging. In addition, perioperative functional status may be difficult to evaluate. Aging produces changes in physiology that are linked to reduced functional reserves and the ability to compensate for physiological stress. As a result, the consumption of several drugs typical of elderly patients can alter the homeostatic mechanism. Elderly patients are at greater risk of long-term functional impairment after the stress of surgery than younger patients. In general, elderly patients with complex medical histories should be given more attention before surgery to ensure that they are properly prepared. All elderly patients should undergo preoperative evaluation and preparation of anesthesia as well as relevant consultations.